Relationship Between Culture, Nutrition during Pregnancy, and Birth Weight of Babies on Stunting in Cawas, Klaten - Atur Semartini; Lilik Ariyanti (Universitas Widya Gama Mahakam Samarinda, 2022)
Background: Stunting is one of children developmental disorders which can cause various developmental disorders in future. Many factors influence the occurrence of stunting, such as parenting, culture, parental background, birth weight, nutrition of pregnant women, and many more. Objectives: This study aims to investigate the relation between culture, nutrition during pregnancy, and birth weight of babies on stunting in Cawas, Klaten. Research Method: This research was an observational analytic study with a cross sectional design. This research was conducted during October-November 2021 in the Working Area of Community Health Center II, Cawas, Klaten and mothers with children aged 2-5 years old as the population. Results: Of 170 respondents, 20% of children suffered from stunting. 20% mothers with basic education had stunting children, 18% mothers who did not work had stunting children 18%, and 20% stunting children were raised in Islam. In addition, this study found that the relationship between the nutritional status of pregnant women and the nutritional status of babies had a significance value of 0.827, the relationship between belief and baby’s nutritional status had a significance value of 0.146, and the relationship between baby’s birth weight status and the current nutritional status of children had a significance value of 0.016. Conclusion: There is a significant relation between stunting and baby’s birth weight, but there is no significant relation between stunting and nutrition during pregnancy and neither culture is.